154k views
2 votes
Solve the equation by elimination

Solve the equation by elimination-example-1

2 Answers

5 votes

Answer:

(1,-7)

Explanation:

y= -9x + 2.............equn(1)

y= -3x - 4..........................(2)

subtract equation (1) from equn. (2)

0= -6x + 6

subtract 6 from both sides

0-6= -6x + 6-6

-6 = -6x

divide via by -6

-6/-6 = -6x/-6

1 = x

to solve for y, put x in any equation

equn.(2)

y= -3x -4

y=-3(1)-4

y= -3-4

y= -7

User MrMage
by
5.2k points
4 votes

Answer:

x = 1, y = -7

Explanation:

Eliminate one of the variables. Subtract:

y = -9x + 2

-(y = -3x - 4)

------------------

To solve, distribute the negative sign (subtraction) to all terms within the parenthesis.

-(y = -3x - 4) = (-y = 3x + 4)

y = -9x + 2

- y = 3x + 4

----------------

0 = -6x + 6

Isolate the variable, (x). Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS. First, subtract, then divide.

0 (-6) = -6x + 6 (-6)

0 - 6 = -6x

-6x = -6

(-6x)/-6 = (-6)/-6

x = 1

Plug in 1 for x in one of the equations.

y = -9x + 2

y = -9(1) + 2

y = -9 + 2

y = -7

x = 1, y = -7

~

User Uder Moreira
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.